Screening for Sugarcane Root Phenes Reveals That Reducing Tillering Does Not Lead to an Increased Root Mass Fraction - Pierre, Johann S.; Perroux, Jai M.; Rae, Anne L. (Frontiers in Plant Science, 2019)
Sugarcane root systems are poorly studied and understood due to the perennial nature, tall stature, and the long cropping cycle. Whilst some field studies gave insights into sugarcane root traits, there is no detailed description of root and root system traits available. The objectives of our work were to establish a baseline of sugarcane root trait values that will serve for future studies, and to characterise the degree of root system resilience when restricting tiller number. We first conducted an initial screening for root trait diversity on a collection of twenty cultivars representative of sugarcane breeding from 1930 to now. Then we investigated the effect of reduced tillering, via manual de-tillering, on the plant root and root system traits of five varieties grown under optimal conditions in a glasshouse for 1700 °Cd. In addition to establishing baseline means and variation for sugarcane root trait values that could serve as a reference for crop models, we demonstrated that the sugarcane root mass fraction was extremely resilient to drastic reduction in tiller number. Restricted plants were effectively maintaining their root system configuration (opening angle) by dramatically increasing the number of nodal roots produced per tiller as well as maximizing total root length by increasing the specific root length. Using this knowledge of sugarcane root traits in combination with the specific agronomic constraints for sugarcane will now underpin the development of a root system ideotype for sugarcane to enable targeted root trait selection for improving crop productivity.